Associations between polymorphisms in folate-metabolizing genes and pancreatic cancer risk in Japanese subjects. Issue 1 (December 2016) - Nakao, Haruhisa; Wakai, Kenji; Ishii, Norimitsu; Kobayashi, Yuji; Ito, Kiyoaki; Yoneda, Masashi; Mori, Mitsuru; Nojima, Masanori; Kimura, Yasutoshi; Endo, Takao; Matsuyama, Masato; Ishii, Hiroshi; et al.
Abstract Background Evidence supporting the associations between folate metabolizing gene polymorphisms and pancreatic cancer has been inconclusive. We examined their associations in a case-control study of Japanese subjects. Methods Our case-control study involved 360 newly diagnosed pancreatic cancer cases and 400 frequency-matched, non-cancer control subjects. We genotyped four folate metabolizing gene polymorphisms, including two polymorphisms (rs1801133 and rs1801131) in the methylenetetrahydrofolate (MTHFR ) gene, one polymorphism (rs1801394) in the 5-methyltetrahydrofolate-homocysteine methyltransferase reductase (MTRR) gene and one polymorphism (rs1805087) in the 5-methyltetrahydrofolate-homocysteine methyltransferase (MTR) gene. Genotyping was performed using Fluidigm SNPtype assays. Unconditional logistic regression methods were used to estimate odds ratios (ORs) and 95 % confidence intervals (CIs) for the associations between folate metabolizing gene variants and pancreatic cancer risk. Results Overall we did not observe a significant association between these four genotypes and pancreatic cancer risk. For rs1801133, compared with individuals with the CC genotype ofMTHFR C677T, the OR for those with the CT genotype and TT genotype was 0.87 (0.62-1.22) and 0.99 (0.65-1.51), respectively. For rs1801131, individuals with the CC genotype had approximately 1.2-fold increased risk compared with those with the AA genotype, but the association was not statistically significant. In analyses stratified by smoking and drinking status, no significant associations were noted for C677T genotypes. No significant interactions were observed with smoking and drinking with respect to pancreatic cancer risk. Conclusions Our data did not support the hypothesis thatMTHFR polymorphisms or other polymorphisms in the folate metabolizing pathway are associated with pancreatic cancer risk.